Traumatic inflammatory response: pathophysiological role and clinical value of cytokines - Rui Li; Jing Jing Ye; Lebin Gan; Mengwei Zhang; Diya Sun; Yongzheng Li; Tianbing Wang; Panpan Chang (2023)
Severe trauma is an intractable problem in healthcare. Patients have a widespread immune system response that is complex and vital to survival. Excessive inflammatory response is the main cause of poor prognosis and poor therapeutic effect of medications in trauma patients. Cytokines are signaling proteins that play critical roles in the body's response to injuries, which could amplify or suppress immune responses. Studies have demonstrated that cytokines are closely related to the severity of injuries and prognosis of trauma patients and help present cytokine-based diagnosis and treatment plans for trauma patients. In this review, we introduce the pathophysiological mechanisms of a traumatic inflammatory response and the role of cytokines in trauma patients. Furthermore, we discuss the potential of cytokine-based diagnosis and therapy for post-traumatic inflammatory response, although further clarification to elucidate the underlying mechanisms of cytokines following trauma is warranted.